TERAPI OUTBOUND SEBAGAI UPAYA MENINGKATKAN NILAI KARAKTER INTEGRITAS PADA SISWA SMP NEGERI 5 PEKANBARU - Novitasari Novitasari; Zulfan Saam; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study aims to determine the differences in the integrity character values of students before and after outbound therapy is given, and to know the effect of outbound therapy to improve the integrity character values in students. Research conducted at SMP Negeri 5 Pekanbaru on 20 subjects with a purposive sampling technique. The study design was pre-experimental with one group pre-test post-test. The data collection instruments used are instruments consisting of indicators of integrity character values. The results showed that there were differences in the level of integrity of students before and after being given Outbound therapy with a significance value of 0,00 < α 0.05. The integrity character values of students who were the subject of research 20 students who were previously in the low category after being given outbound therapy were mostly in the moderate category. In addition, based on the Spearman rank test, it is known that there is a significant influence of Outbound therapy on the integrity character value of students, which is 22.5% while 77.5% is influenced by other factors originating from outside and within the student. Key Words: Outbound Therapy, Integrity Character Value